The Impact of Layoff Announcements on Shareholders - Ursel, Nancy; Armstrong-Stassen, Marjorie (Relations industrielles / Industrial Relations, 1995)
This study explores the reactions of shareholders to layoff announcements. We examine shareholders' reactions to 137 layoff announcements by 57 Canadian firms over the period January 1989 to August 1992. Shareholders are found to react negatively to announcements of a layoff in their company. Shareholders have a greater negative reaction to a company's first layoff than to subsequent layoff announcements. Moreover, shareholders respond more negatively to large-scale layoffs than to those involving small percentages of the workforce. The implications of thèse findings for human resource management are discussed.